2012
DOI: 10.1186/1471-2458-12-30
|View full text |Cite
|
Sign up to set email alerts
|

Are marginalized women being left behind? A population-based study of institutional deliveries in Karnataka, India

Abstract: BackgroundWhile India has made significant progress in reducing maternal mortality, attaining further declines will require increased skilled birth attendance and institutional delivery among marginalized and difficult to reach populations.MethodsA population-based survey was carried out among 16 randomly selected rural villages in rural Mysore District in Karnataka, India between August and September 2008. All households in selected villages were enumerated and women with children 6 years of age or younger un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 12 publications
2
56
1
1
Order By: Relevance
“…Muslim and scheduled caste women were less likely to deliver their three most recent births in an institution. For the other two recent births, religion was not a significant predictor -a finding that is consistent with earlier studies (Mekonnen and Mekonnen, 2002;Saroha, Altarac, and Sibley, 2008). The observation that Muslim women sought less assistance from medical settings is likely to be attributed to their religious beliefs, cultural norms, and traditional practices (Ganle, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Muslim and scheduled caste women were less likely to deliver their three most recent births in an institution. For the other two recent births, religion was not a significant predictor -a finding that is consistent with earlier studies (Mekonnen and Mekonnen, 2002;Saroha, Altarac, and Sibley, 2008). The observation that Muslim women sought less assistance from medical settings is likely to be attributed to their religious beliefs, cultural norms, and traditional practices (Ganle, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, rates of institutional deliveries were 96.0%, much higher than reported in 85.8% rural Karnataka and other studies [10]. These differences could be due to the variability in time demographic composition studied in these surveys.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, higher antenatal care coverage has been associated with lower rates of antepartum stillbirth [12]. In this study, a vast majority (98.9%) of women reported at least one antenatal visit, which is higher than other studies in the state (93.4%) and 93.1% reported for rural Karnataka in the 2012–2013 DLHS-4 [9, 10]. Although the rates of antenatal reach in this study seem to be high, the frequency of visits per woman appear to be teetering on the edge of the World Health Organization’s (WHO) recommended four antenatal visits [15], ranging between an average of 2.7–7.6.…”
Section: Discussionmentioning
confidence: 62%
“…These deaths and injuries are partly due to inadequate utilization and poorquality maternal health care, -antenatal care, -skilled attendance at birth and postnatal care [5,6] and are entirely preventable through increased utilization of skilled maternal healthcare services [3]. In addition these mortality have been associated with maternal education, maternal age and autonomy of the mother [7][8][9]. Several studies have shown that skilled birth attendants during labour, delivery and the early postpartum period can reduce significant number of maternal and newborn deaths through provision of timely obstetric and newborn care [10].…”
Section: Issn: 2320-5407mentioning
confidence: 99%